Enhancing Classroom Learning through Hybrid Teaching and Learning: Insights from a Four-Session Training Program - Badarudin, Badarudin; Wiarsih, Cicih; Nofiana, Mufida; Risnani, Listika Yusi; Tek, Ong Eng (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2023)
Hybrid learning, with a focus on facilitating students’ problem-solving skills, is a new and innovative approach which teachers can employ to inculcate higher-level thinking among their students. Accordingly, the purpose of this hybrid training program is to equip teachers with the skills to create hybrid learning instruments that facilitate problem-solving in their classrooms. The training methods include presentations, Q&A sessions, discussions and performances in the form of direct exercises guided by a facilitator (or resource person). Offline teachers from Madrasah Ibtidaiyah (MI) Muhammadiyah Kramat and online teachers from a primary school, or Sekolah Dasar (SD) MI Muhammadiyah Se-Banyumas attended the training. In general, training activities are structured into 4 stages, namely (1) training on creating instruments and implementing hybrid learning to support problem-solving; (2) assisting in the creation of hybrid learning instruments; 3) monitoring, testing, and implementing hybrid learning in the classroom; and 4) reflecting on the outcomes of implementing hybrid learning. Insights gained from the training program that aims to create hybrid learning instruments, are presented and discussed.